2017
DOI: 10.1016/j.socscimed.2017.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Do restrictive omnibus immigration laws reduce enrollment in public health insurance by Latino citizen children? A comparative interrupted time series study

Abstract: In the United States, there is concern that recent state laws restricting undocumented immigrants’ rights could threaten access to Medicaid and the Children’s Health Insurance Program (CHIP) for citizen children of immigrant parents. Of particular concern are omnibus immigration laws, state laws that include multiple provisions increasing immigration enforcement and restricting rights for undocumented immigrants. These laws could limit Medicaid/CHIP access for citizen children in immigrant families by creating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Fourth, we notice that several states also passed omnibus immigration laws that were similar to SB 1070 and later blocked from implementation. We exclude the states that passed omnibus immigration laws from the control pool based on the study of Allen and McNeely (2017). The results of different sample selection tests are consistent with the main results and are shown in Table 1.…”
Section: Data and Empirical Methodsmentioning
confidence: 99%
“…Fourth, we notice that several states also passed omnibus immigration laws that were similar to SB 1070 and later blocked from implementation. We exclude the states that passed omnibus immigration laws from the control pool based on the study of Allen and McNeely (2017). The results of different sample selection tests are consistent with the main results and are shown in Table 1.…”
Section: Data and Empirical Methodsmentioning
confidence: 99%
“…Consequently, increasing deportation rates have been associated with reductions in enrollment in both the Medicaid and the Women, Infant, and Children (WIC) program among noncitizens (130, 132, 141). Reflecting the negative health consequences of increased psychosocial stress, workplace raids, increasing deportation rates, and the fear of deportation have also been significantly associated with: (1) increased poor general health, (2) poor cardiovascular health, (3) self-reported mental health problems, (4) food insecurity, (5) delays in receiving prenatal care, and (6) increases in low birthweight babies among Hispanics/Latinos, especially among those who are foreign-born Hispanic/Latino noncitizens (31, 34, 72, 86, 102, 106, 120, 133, 140). Finally, IE activities have also been associated with reduced K-12 school completion, reduced employment, increased childhood poverty, and an increased reticence to trust the judicial system and report crimes (7, 8, 67, 90).…”
Section: Immigration Enforcement: Workplace Raids and Deportationsmentioning
confidence: 99%
“…National studies also show that perceptions of restrictive immigrant policies and anti-immigrant sentiments in a state are associated with higher mortality, poorer self-reported health, and poorer mental health among Hispanic/Latino adults and children, especially those in mixed-status families (54, 79, 133, 135). These changes in utilization and health occurred despite limited and inconclusive evidence from national studies that restrictive state immigrant policies reduce health insurance coverage or that inclusive state immigrant policies improve health insurance coverage (5, 147).…”
Section: State and Local Immigrant Policiesmentioning
confidence: 99%
“…Some studies found decreased health care utilization (Beniflah et al, 2013; Toomey et al, 2014) and enrollment in public benefits (Toomey et al, 2014) among Latino children. Others found no decrease in health department visits (Koralek et al, 2009; White et al, 2014a) or enrollment in public benefits (Allen & McNeely, 2017; Koralek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most restrictive state immigrant laws, called omnibus immigrant laws, combine three or more immigration-related measures in a single bill (Laglaron et al, 2008). Colorado, Indiana, Nebraska, and Oklahoma each passed one omnibus law between 2005–2014; Alabama, Arizona, Georgia, Missouri, South Carolina, and Utah passed two or more (Appendix Table 1) (Allen & McNeely, 2017). In all 10 states, omnibus laws increased local enforcement of federal immigration law, restricted undocumented immigrants’ access to employment, and expanded restrictions on undocumented immigrants’ access to public benefits.…”
Section: Introductionmentioning
confidence: 99%